Utilizing quality by design methodology for liquid chromatography method development and validation in quantifying impurities in Pitolisant, a Histamine-3 (H3) receptor antagonist/inverse agonist - Jayaprakash Kanijam Raghupathi; Lova Gani Raju Bandaru; Kiran Kumar Madineni; Mastan Ali Syed; Sreekantha Babu Jonnalagadda; D. Ramachandran; Naresh Kumar Katari (Results in Chemistry)
We developed and validated a liquid chromatography technique to determine organic impurities of Pitolisant in Pitolisant film-coated tablets (4.45 mg and 17.8 mg), a medication used to treat excessive daytime drowsiness. The method uses a gradient elution process on an Inertsil ODS-3 V column (250 mm × 4.6 mm, 3 μm), with a flow rate of 0.8 mL/min and detects substances at 210 nm. The analytical parameters consist of a sample injection volume of 10 μL, a sample temperature of 10 °C, and an analytical column compartment temperature of 55 °C. mobile phase A is made up of 70 mM sodium perchlorate monohydrate at a pH of 2.0 mixed with acetonitrile in a 75: 25 ratio, while mobile phase B is a mix of methanol and water in a 90:10 ratio. The recovery rate of impurities ranges from 98.9 % to 104.9 %. All impurities exhibited excellent linearity, with correlation values (r2) of 0.9987 or 0.9999. The method's stability-indicating nature was evaluated through forced degradation studies. Its robustness was assessed using a full factorial design, and we identified the method's operable design space.